Design and Development of a Spatial Immersive Track Cycling Simulator - Hwa, Jen Yap (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe